Penerapan Aplikasi Si Apik (Sistem Aplikasi Pencatatan Informasi Keuangan) Pada UMKM Olahan Cokelat - Destriana Safitri; Darman Darman ; Muslimin Muslimin; Wiri Wirastuti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the application of the Siapik Application to MSMEs, whether the Si Apik Application can make it easier for users to make accurate financial reports and be able to solve financial problems in chocolate-processed MSMEs. The method used in the research is using a qualitative descriptive method, with data collection techniques using direct observation techniques at the research location and conducting interviews. The data source was obtained from primary data. The research results show that the Si Apik application makes it easy for chocolate-processed MSMEs, especially CV Rapoviaka Simple, in making financial reports because the features in the application are complete and the Si Apik application really has a positive impact on MSMEs who are running their businesses.